Characterization of the novel HLA‐DPA1*01:03:19 allele by sequencing‐based typing. (12th February 2020) - Cargou, Marine; Andreani, Marco; Locatelli, Franco; Blouin, Laura; Visentin, Jonathan
Abstract : HLA‐DPA1*01:03:19 differs from DPA1*01:03:01:02 by one nucleotide substitution in codon 190 in exon 4.